Bio-Distribution of Pancreas-Derived Exosomes - Sara Raquel Sousa Alves (2024)
Exosomes, a subtype of extracellular vesicles (EVs), are nanoparticles released by all cell types that play a crucial role in intercellular communication. Despite their importance in both pathological and non-pathological processes, the dynamics of exosomes within living systems remain poorly understood. Pancreatic ductal adenocarcinoma (PDAC), a highly lethal disease with a 5-year survival rate of only 13%, has been shown to involve EVs in its establishment, maintenance, and progression. In this thesis, a genetically engineered mouse model (ExoBow) was used to map the spatiotemporal biodistribution of pancreas-derived exosomes in both non pathological and PDAC-affected mice. It was successfully confirmed the size, identity, and purity of exosomes secreted by PDAC cell lines transfected with the ExoBow transgene. However, ex vivo analysis of mouse PDAC cell lines revealed variability in exosome secretion rates, likely reflecting tumor heterogeneity. As PDAC progressed, a gradual increase in the intensity and quantity of pancreas-derived exosome communication was observed, with fluctuations in exosome distribution in non-pathological contexts in 8-, 17-, and 30-week-old mice. In healthy mice, pancreas-derived exosomes exhibited organotropism, preferentially targeting immune organs such as the thymus at 8 weeks and the spleen at 30 weeks. Using another GEMM designed to block exosome secretion, it was found that the absence of exosomes did not affect the structural integrity of the thymus at 17 weeks. The development of this novel GEMM allows for the endogenous mapping of exosome secretion, providing new insights into how exosome production is influenced by age, homeostatic or disease stage. This information is significant for the advancement in the field of EV research and offers a valuable tool for further exploration of exosome-mediated communication.